The Theme of Freedom in Contemporary African American Literature: A Stylistic Study of Maya Angelou's I Know Why The Caged Bird Sings - ALAHOUM, Ikram; SAKER, Ilham (جامعة الوادي - University of Eloued, 2023)
The present research intends to shed light on the recurrent concept of freedom in contemporary African American literary texts. Specifically, a stylistic analysis is conducted on Maya Angelou's I Know Why the Caged Bird Sings. The present study endeavors to employ a descriptive-analytical approach to analyze the stylistic portrayal of freedom in Maya Angelou's literary work, I Know Why the Caged Bird Sings. The objective of this investigation is to scrutinize the utilization of language and literary devices used by the author in portraying the concept of freedom within the selected corpus. The research argues that Maya Angelou skillfully employs a diverse range of literary devices to effectively convey her vision of freedom from the unique perspective of an African American who has personally endured racial oppression. Maya Angelou has employed various stylistic devices and deviations in her writings, such as lexical deviation and figurative language. The present study is interested in the linguistic and stylistic features present in the works of Maya Angelou that underscore the theme of freedom. Specifically, the analysis elucidates how these features manifest in Angelou's novel I Know Why the Caged Bird Sings, wherein the pursuit of personal freedom persists despite adversities. The study finds that Maya Angelou used a unique style to portray the idea of freedom. يهدف البحث الحالي إلى إلقاء الضوء على المفهوم المتكرر للحرية في النصوص الأدبية الأفريقية الأمريكية المعاصرة. على وجه التحديد ، تم إجراء تحليل أسلوبي لرواية مايا أنجيلو "أنا أعرف لماذا يغني الطائر المسجون في قفص". تسعى الدراسة الحالية إلى استخدام المنهج الوصفي التحليلي لتحليل الصورة الأسلوبية للحرية في عمل مايا أنجيلو الأدبي. الهدف من هذا التحقيق هو التدقيق في استخدام اللغة والأدوات الأدبية من قبل المؤلف في تصوير مفهوم الحرية داخل المجموعة المختارة. ويذهب البحث إلى أن مايا أنجيلو تستخدم بمهارة مجموعة متنوعة من الأدوات الأدبية لكي تنقل بفعالية رؤيتها للحرية من منظور فريد لأمريكية أفريقية عانت شخصياً من القمع العنصري. وقد استخدمت مايا أنجيلو أجهزة وأوجه انحراف مختلفة في كتاباتها، مثل الانحراف اللغوي واللغة المجازية. وتهتم هذه الدراسة بالسمات اللغوية والاسلوبية التي تنطوي عليها أعمال مايا أنجيلو التي تؤكد على موضوع الحرية. على وجه التحديد، يوضح التحليل كيف تظهر هذه السمات في رواية أنجيلو أعرف لماذا يغني الطائر المسجون في قفص حيث لا يزال السعي للحرية الشخصية مستمراً على الرغم من الشدائد. وتوصلت الدراسة إلى أن مايا أنجيلو استخدمت أسلوبا فريدا لتصوير فكرة الحرية.
Master’s Degree in Literature and Civilization
Keywords: Contemporary African American Literature, Freedom, Stylistics, Maya Angelou, African American.; الأدب الأفريقي الأمريكي المعاصر ، الحرية ، الأسلوب ، مايا أنجيلو ، أمريكي من أصل أفريقي.